Can the invisible welfare state redistribute? - Isaac William Martin (economic sociology_the european electronic newsletter, 2020)
In the past three decades, scholars of welfare policy in the United States have come to recognize tax privileges as an important part of the US social policy regime. A tax privilege is a provision of law or customary practice that grants favorable treatment to particular activities or categories of persons by excusing them from specified tax obligations to which they would normally be subject. Scholars have documented a great number and variety of formal and informal tax privileges provided by federal, state, and local governments.
Keywords: 300